Impact of smoking status on the efficacy of inhaled corticosteroids in chronic obstructive pulmonary disease: a systematic review - Roger Knaggs; Kimberley Sonnex; Hanna Alleemudder (BMJ Open)
Objectives Inhaled corticosteroids (ICS) reduce exacerbation rates and the decline in lung function in people with chronic obstructive pulmonary disease (COPD). There is evidence that smoking causes ‘steroid resistance’ and thus reduces the effect of ICS. This systematic review aimed to investigate the effect of smoking on efficacy of ICS in COPD in terms of lung function and exacerbation rates.Design Systematic review.Data sources An electronic database search of PubMed, Ovid MEDLINE, Ovid Embase and Cochrane Library (January 2000 to January 2020).Eligibility criteria Fully published randomised controlled trials (RCTs), in the English language, evaluating the use of ICS in COPD adults that stratified the participants by smoking status. Trials that included participants with asthma, lung cancer and pneumonia were excluded. The primary outcome measures were changes in lung function and yearly exacerbation rates.Data extraction and synthesis Two independent reviewers extracted data and assessed risk of bias using the Cochrane Collaboration’s tool.Results Seven studies were identified. Four trials (17 892 participants) recorded change in forced expiratory volume in one second (FEV1) from baseline to up to 30 months after starting treatment. Heavier smokers (>36 pack years) using ICS had a greater decline in FEV1 that ranged from −22 mL to −75 mL in comparison to lighter smokers. Smokers using ICS had mixed results in FEV1 change: −8 mL to +77 mL in comparison to ex-smokers. Four trials (21 270 participants) recorded difference in COPD exacerbation rates at 52 weeks. The rate ratios favoured more exacerbations in ICS users who were current or heavier smokers than those who were ex-smokers or lighter smokers (0.81 to 0.99 vs 0.92 to 1.29).Conclusions In COPD, heavier or current smokers do not gain the same benefit from ICS use on lung function and exacerbation rates as lighter or ex-smokers do, however effects may not be clinically important.PROSPERO registration number CRD42019121833